DETERMINASI PENGGUNAAN LAYANAN MOBILE BANKING DENGAN FAKTOR SOSIAL SEBAGAI VARIABEL MEDIASI PADA BANK SYARIAH INDONESIA - Shafa Aqilah, (2021)
This study aims to prove the factors that influence a person's decision to use mobile banking. In this study, the variables used were perceived usefulness, perceived ease of use, perceived credibility as exogenous variables and social factors as mediators. This research uses quantitative methods. The population in this study are Indonesian Sharia Bank customers who use BSI mobile services in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas. The number of samples collected as many as 200 people obtained by purposive sampling method. The analysis technique used is the inner model, outer model and hypothesis testing using SmartPLS 3.2.9. The results obtained in this study prove that perceived usefulness has a significant effect on decisions to use mobile banking, perceptions of ease of use have no significant effect on decisions to use mobile banking and perceptions of credibility have a significant effect on decisions to use mobile banking. Meanwhile, this study proves that social factors do not succeed in mediating other variables in the decision to use mobile banking.